2011
DOI: 10.1088/0031-9155/56/19/008
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory monitoring with an acceleration sensor

Abstract: Respiratory gating radiotherapy is used to irradiate a local area and to reduce normal tissue toxicity. There are certain methods for the detection of tumor motions, for example, using internal markers or an external respiration signal. However, because some of these respiratory monitoring systems require special or expensive equipment, respiratory monitoring can usually be performed only in limited facilities. In this study, the feasibility of using an acceleration sensor for respiratory monitoring was evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Documented measurements often diverge from accurately counted ones [ 7 ]. While there are respiratory sensors in development using a range of methods very little data is available on usage outside of controlled laboratory settings [ 16 , 17 , 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Documented measurements often diverge from accurately counted ones [ 7 ]. While there are respiratory sensors in development using a range of methods very little data is available on usage outside of controlled laboratory settings [ 16 , 17 , 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was called “human observation”, since an expert provided a value of the breathing parameter from direct observation of the signals recorded by the sensors. Figure 28 shows that validation using a reference device was the predominant approach (adopted by 67% of the studies that performed validation), followed by the use of an artificial validation prototype (10%) [ 69 , 74 , 77 , 90 , 93 , 97 , 110 , 114 , 116 , 119 , 123 , 135 , 141 , 146 , 150 , 226 ]. It is also worth noting that 53 studies presented the sensing systems without providing evidence of their validation.…”
Section: Resultsmentioning
confidence: 99%
“…The average period error was 2.9 ms, and the average amplitude error was 49.4 μm. In 2011, Ono et al [ 30 ] reported the performance of a MEMS angular velocity sensor-based respiration monitoring system. They reported that the maximum difference of the system was 4.3%, the average periodic error was 46.7 ms, and the average amplitude error was 363.3 μm.…”
Section: Discussionmentioning
confidence: 99%